(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The present study aims to extend previous systematic reviews on mand training to children and adolescents with ASD. Based on PRISMA’s recommendations for summarizing reviews, 521 papers were initially found on national and foreign databases, between 2015 and 2019. Twelve papers were selected after the inclusion and exclusion criteria were applied, focusing on applied researches with detailed results and methods description. The results indicate that heterogeneity in the procedures has an impact on the integrity of the studies among the works of different sources. Many studies do not include procedures to promote generalization and maintenance of target behavior or evaluate it. The studies have children as participants, and the most used experimental design is multiple-baseline across participants. The teaching procedure and the types of prompts vary considerably between the studies. Discussion with previous literature reviews and possible implications for the more rigorous planning of mand teaching procedures are considered.